Engine Speed Control of Excavator With PID Method - Jun Zhang; Shengjie Jiao; Guimao Si; Xuepeng Cao; Min Ye; Jinping Li; Xinxin Xu; Daopei Zhang (Institute of Advanced Engineering and Science, 2014)
Distinction work task power-matching control strategy was adapted to excavator for improving fuel efficiency; the accuracy of rotate engine speed at each work task was core to excavator for saving energy. 21t model excavator ZG3210-9 was taken as the study object to analyze the rotate speed setting and control method, linear position feedback throttle motor was employed to control the governor of engine to adjust rotate speed. Improved double closed loop PID method was adapted to control the engine, feedback of rotate speed and throttle position was taken as the input of the PID control mode. Control system was designed in CoDeSys platform with G16 controller, throttle motor control experiment and engine auto control experiment were carried on the excavator for tuning PID parameters. The result indicated that the double closed-loop PID method can take control and set the engine rotate speed automatically with the maximum error of 8 rpm. The linear model between throttle feedback position and rotate speed is established, which provides the control basis for dynamic energy saving of excavator. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4917